The Relationship Between Mosquito Nest Eradication Practice and The Existence of Larvae Aedes Aegypti with Dengue Incidence in Penjaringan District, North Jakarta - Nurdin Nurdin; Martini Martini; Mursid Raharjo; Siti Hajar Husni (Jurnal Penelitian Pendidikan IPA, 2023)
Dengue Hemorrhagic Fever (DHF) is a public health problem in Indonesia and still often causes extraordinary events with a high mortality rate. All regions in Indonesia are at risk of contracting dengue disease, because the virus that causes and mosquitoes has spread widely in residential and public places in Indonesia. Penjaringan District North Jakarta City has 70% densely populated residential areas, so it has a risk for dengue disease transmission. The sample in this study amounted to 80 people, with a division of 40 case groups and 40 control groups. This research uses observational analytical design with case control method. The variables studied were Mosquuito Nest Eradication practice and the presence of larvae. Data on Mosquuito Nest Eradication Behavior-DHF variables were obtained through questionnaires and variable data on the presence of larvae were obtained through direct observation of the environment around the respondent's house. Based on the results of Chi Square analysis showed that the practice of Mosquuito Nest Eradication (p = 0.007) and the presence of larvae (p = 0.047) had a significant relationship. Respondents who are lacking in Mosquuito Nest Eradication practice are at 5,952 times greater risk of developing DHF compared to people who are good in Mosquuito Nest Eradication practice. There is a relationship between the practice of Mos and the existence of larvae with dengue incidence in densely populated settlements in Penjaringan District, North Jakarta. The community should pay attention to the eradication of their nest by conducting the 3M Plus program regularly